PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MODEL PEMBELAJARAN SCRAMBLE UNTUK MATERI SISTEM ORGANISASI KEHIDUPAN PADA PEMBELAJARAN IPA KELAS VII SMP - Novita, '; Darmawati '; Irda Sayuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this research is to produce student working sheet based on scramble learning model for the chapter of living organization system on Science subject in class VII of junior high school. This development research was conducted at Laboratoryof Biology Education Departement of PMIPA Facult of Teaching And education University of Riau and SMPN 8 Pekanbaru. This research was conducted on March to june 2017. Research type that used this development research refer into Research and Development approach by using ADDIE model that has 5 steps (analyze, design, development, implement, evaluate). This research was done until development step only. Instument that used is validation sheet and respondent cuesionary, next it was held a limited test to 15 people Biology Education Study and 25 7th grade pipils in SMPN 8 Pekanbaru. Research data was analyzed by using descriptive. Analysist on come of LKPD based by scramble learning model for the chapt of living organization system was seen by 3 aspects, content feasibility aspect, planning aspect, and pedagogical aspect. Validity value LKPD based by scramble learning model in content feasibility aspect was 3,14 with valid category, validity value in planning aspect was 3,22 with valid category, whereas validity value in pedagogical aspect was 3,08 with category valid. Response learners by pupil on LKPD based by scramble learning model was categoryzed into very good with 3,34 score.Key Words: Development, Student Worksheet, Scramble Learning Model